Whistleblowers and Outcomes of Financial Misrepresentation Enforcement Actions - CALL, ANDREW C.; MARTIN, GERALD S.; SHARP, NATHAN Y.; WILDE, JARON H. (Journal of Accounting Research, 2018)
ABSTRACT Whistleblowers are ostensibly a valuable resource to regulators investigating securities violations, but whether there is a link between whistleblower involvement and the outcomes of enforcement actions is unclear. Using a data set of employee whistleblowing allegations obtained from the U.S. government and the universe of enforcement actions for financial misrepresentation, we find that whistleblower involvement is associated with higher monetary penalties for targeted firms and employees and with longer prison sentences for culpable executives. We also find that regulators more quickly begin enforcement proceedings when whistleblowers are involved. Our findings suggest that whistleblowers are a valuable source of information for regulators who investigate and prosecute financial misrepresentation.